Strategi Adaptasi Masyarakat Terhadap Perubahan Lingkungan Akibat Penambangan Batu Gamping di Flores - Do Rosario Da Cruz Mariano, Rivelino Jonathan; Pereira Maia Pinto, Gaspar (Blueprint Journal, 2025)
Limestone mining in Flores has had significant impacts on the environment and local communities. Communities face a variety of challenges, including ecosystem damage, changes in soil quality, and socio-economic impacts. This paper aims to explore the adaptation strategies implemented by the Flores community in dealing with environmental changes due to mining activities. Through a qualitative approach and secondary data analysis, this study identifies various adaptation strategies, ranging from sustainable natural resource management to strengthening community capacity in dealing with mining impacts. The results show that although communities have adopted several adaptation strategies, there are still major challenges that must be overcome to achieve environmental and social sustainability.